Pyrazinamide-induced maculopapular rash - Khayyam Khalid; Imam Faisal; Sharma Manju; Pillai K; Behera D (Wolters Kluwer Medknow Publications, 2010)
Pyrazinamide is a commonly used first-line antitubercular drug. Gastric-related adverse drug reactions are common with pyrazinamide. Dermatological manifestations due to pyrazinamide are rare. This study aimed find out the dermatological manifestations/adverse drug reaction (ADR) due to pyrazinamide. We reported a case of maculopapular rash caused by pyrazinamide in a patient on antituberculosis treatment using structured questionnaires. The patient developed maculopapular rashes on receiving combination antituberculosis treatment. The rashes disappeared after stopping the suspected drug. The patient was rechallenged with pyrazinamide, which led to reappearance of a similar type of rash. The causality, preventability, and severity were assessed using the Naranjo algorithm and Hartwig scale. Since pyrazinamide is a commonly used drug in tuberculosis and which is a common infectious disease in developing countries, with the similar reports, we can predict early case detection and can prevent the occurrence of similar reactions in future.